MANAGEMENT OF HELLP SYNDROME BEFORE DELIVERY: A SYSTEMATIC REVIEW - Azkiya, Mayla (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
Background: HELLP syndrome, named for 3 features of the disease (hemolysis, elevated liver enzyme levels, and low platelet levels), is a life-threatening condition that can potentially complicate pregnancy. HELLP was once known as edema-proteinuria-hypertension gestosis type B in the early 20th century and was later renamed in 1982 by Louis Weinstein. The aim: This study aims to show management of HELLP syndrome before delivery. Methods: By comparing itself to the standards set by the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020, this study was able to show that it met all of the requirements. So, the experts were able to make sure that the study was as up-to-date as it was possible to be. For this search approach, publications that came out between 2013 and 2023 were taken into account. Several different online reference sources, like Pubmed and SagePub, were used to do this. It was decided not to take into account review pieces, works that had already been published, or works that were only half done. Result: In the PubMed database, the results of our search on SagePub brought up 110 articles. The results of the search conducted for the last year of 2013 yielded a total 23 articles for PubMed and 75 articles for SagePub. The result from title screening, a total 8 articles for PubMed and 28 articles for SagePub. In the end, we compiled a total of 10 papers. We included five research that met the criteria. Conclusion: HELLP syndrome is an important complications in pregnancy which increases maternal and fetal mortality. This disease usually remits with supportive treatment which includes prescription of corticosteroid, magnesium sulfate, stabilization of mother and pregnancy termination. Plasmapheresis is a treatment of choice which improves clinical outcomes in complicated cases.